Efficient microorganisms: an alternative tool for drought management in bean plants? - Santiago, Gabriela de Melo; Cargnelutti, Denise; Castamam, Alfredo (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2022)
The objective was to evaluate the effect of efficient microorganisms (EM) on common bean plants subjected to water stress. Bean plants were cultivated in a greenhouse which were subjected to treatments with different levels pot capacity (CP) (100; 75 and 50% CP) and/or efficient microorganism (EM) in the dilution of 1:20 or 1:100. The variables analyzed were gas exchange, water use efficiency (WUE), fluorescence and chlorophyll concentration, as well as biometric analysis. The data obtained were subjected to analysis of variance and means were compared by Tukey test (p < 0.05). Under severe water stress (50% CP) the photosynthetic rate (A) reduced 77% as well as the stomatal conductance. The treatment with EM 1:100 showed transpiration about 3 times higher than the treatment without EM, carboxylative efficiency 3 times higher and initial fluorescence (F0) 1.2 times higher than the other treatments. Under moderate water stress (75% CP) the A reduced by 64%, plants treated with EM 1:100 increased the unregulated energy (compared to plants without EM incorporation and the values of EM were maintained, WUE by these treatments. At both levels of water stress the non-photochemical regulated energy dissipation in plants increased with the application of EM 1:20 and EM 1:100 compared to the control, both treatments with EM increased the F0 by 1,7 (EM 1:100) and 1.33 (EM 1:20). Plants had reduced height, stem diameter, fresh biomass and dry for all treatments compared to the control (100% CP). The treatments with EM reduced the leaf area and EM 1:20 was superior. Efficient microorganisms promoted possible resistance to water deficit, indicating the need for further studies. It was concluded that the use of EM appears to be promising, requiring further studies regarding its effects.